Robot Operating System (ROS) based simulator for Hexapod system - Toh, Yan Han (2017)
Technological advancements have been agile and steady since the early era of the industrial revolution. Machines are part of everyday life and robots are slowly taking over critical tasks which require precision and incur high risk. This report documents the Robotic Operating System (ROS) usage to create a simulator for a hexapod to test real-time algorithms. The hexapod will replace a person in stipulated scenarios such that it can proceed more effectively and protects the person from any possible risk within the tasks. The Ubuntu/ROS is used to set up this project, utilizing the RVIZ simulator to simulate the hexapod. The hexapod is designed and the gait kinematics is discussed and implemented. The hexapod is put through a series of simulations to test the gait kinematics as implemented while ensuring that stability of the hexapod is maintained such that it will be feasible for real-life stipulated usages.